Transmission of CPRI signals along weakly-coupled multicore fibers for support of 5G networks - Marques, A. S. (2018)
The impact of intercore crosstalk (ICXT) of weakly-coupled multicore fibers on the transmission performance of a Common Public Radio Interface (CPRI) signal in 5G networks is studied by numerical simulation. The results show that forward error correction-supported CPRI signals (accepting higher bit error rates) have more tolerance to ICXT, which increases with the skew between cores. Improvement of the tolerance of CPRI signals to the ICXT, due to the increase of the skew, by 1.7 dB is shown.